Bismuth oxychloride-based materials for the removal of organic pollutants in wastewater. (June 2021) - Yao, Ling; Yang, Hui; Chen, Zhongshan; Qiu, Muqing; Hu, Baowei; Wang, Xiangxue
Abstract: Various kind of organics are toxic and detrimental, resulting in eutrophication, black, odorous water and so on. Photocatalysis has been deemed to be a promising technology which can decompose different kinds of organic pollutants under visible light irradiation, finally achieving non-poisonous, harmless CO2, water and other inorganic materials. Bismuth oxychloride (BiOCl) is considered as a promising photocatalyst for the efficient degradation of organic pollutants due to its high chemical stability, unique layered structure, resistance to corrosion and favorable photocatalytic property. However, BiOCl can only absorb UV irradiation because of its wide band gap of 3.2 eV–3.5 eV that limits its photocatalytic performance. Herein, a lot of methods have been reviewed to improve its photocatalytic activity. We introduced the unique and special layered structure of BiOCl, the typical and common synthesis methods that can control the morphology, and the most important part is varies of modification routes of BiOCl and the application of BiOCl-based materials for photocatalytic degradation of organic pollutants. Besides, we summarized the crucial issues and perspectives about the application of BiOCl in pollution management. Graphical abstract: Image 1 Highlights: The synthesis methods of BiOCl-based composites are reviewed. Metal-doping, nonmetal-doping and OVs introduction functions are summarized. Recent catalytic applications of BiOCl-based photocatalysts are discussed. The mechanisms of BiOCl-based photocatalysts are analyzed in catalysis.